Software in the Loop for the implementation of an autopilot system for fixed-wing aircrafts - Quiroz Villalobos, Lennin Paul (2020)
When you want to develop and test software products for complex systems such as airplanes, space shuttles, satellites, automobiles or nuclear plants, one of the biggest drawbacks is the availability of the physical system, due to the great complexity, risks and costs involved in performing tests on the real system. Software in the Loop (SITL) allows us to test algorithms, source code or control strategies for complex systems within a simulation that contains the mathematical model of the real physical system. This research work proposes the use of a Software in the Loop platform for the development of an autopilot system for a fixed-wing aircraft. The architecture of the implemented application, the software design process, the protocols used, the control strategies, the programming techniques, the results obtained and the conclusions are shown herein.